Assessment Of Customer Satisfaction Using Serqual Instrument With Special Reference To The Malaysian Timber Industry Board (MTIB) And Its Timber Verification Services (TVS) - Mohd Noor, Mohd Nazri (2005)
This study examines the level of customer satisfaction with special reference to Timber Verification Services (TVS) rendered by The Malaysian Timber Industry Board (MTIB) using SERVQUAL dimensions as the instrument.